mRNA COVID-19 vaccine: A future hope for cancer treatment - Yadav, Ajay Kumar; Gnawali, Suman; Mandal, Sandip; Shrestha, Gyan Bahadur; Yuan, Gangbiao (Journal of Biomedical Sciences, 2021)
Background: mRNA vaccines have a strong potential for a possible cancer therapy platform. They express tumor antigens in antigen-presenting cells (APCs) after immunization, facilitating innate/adaptive immune stimulation. Because of its high effectiveness, safe administration, rapid development potential, and cost-efficient manufacturing, the mRNA cancer vaccine surpasses other traditional vaccination platforms. Conclusion: Careful evaluation of promising mRNA vaccines to supervise as carriers of lipids for cancer patients needs to be done. In addition, a possible revaluation for optimal protection is required. However, the extent to which solid tumours might take a significant part of the vaccine doses is still unknown.